THE EFFECTIVENESS OF USING GAMES TO IMPROVE STUDENTS’ VOCABULARY LEARNING AT SMP NEGERI 3 TONDANO - Pasande, Restiani Daud; Samola, Nurmin; Hampp, Paula L. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research focuses on the effectiveness of using games to increase student vocabulary learning at SMP Negeri 3 Tondano. The research sample consisted of 44 students from classes VII A and VII B. The research method used was quantitative using a True-Experimental pre-test and post-test control group design. The instruments used in this research were multiple-choice tests. Data were analyzed using the average score formula to see significant differences between pre-test and post-test scores. The research results showed that there was a significant difference between the pretest and posttest scores. The pre-test results for the experimental class were 41.14 and the post-test were 86.82. The difference in scores between the pre-test and post-test is 39,54. and the pre-test result from the control class was 40,68 and the post-test was 69,77. The difference in scores in the control class was 31,37. The research results showed that the average post-test score in the experimental class was higher than the initial test. and data analysis using N-Gain Score shows that in the experimental class, an average score of 77,6 % was obtained, including the effective category. And in the control class (not using puzzle games) 53.52% were in the less effective category. So providing learning treatment using games, is effective in increasing students' vocabulary learning.